2010
DOI: 10.1152/ajpgi.00092.2010
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of myenteric neurochemical phenotype and impact on neuromuscular transmission in the rat colon

Abstract: de Vries P, Soret R, Suply E, Heloury Y, Neunlist M. Postnatal development of myenteric neurochemical phenotype and impact on neuromuscular transmission in the rat colon. Am J Physiol Gastrointest Liver Physiol 299: G539 -G547, 2010. First published June 3, 2010 doi:10.1152/ajpgi.00092.2010.-Profound changes in intestinal motility occur during the postnatal period, but the involvement of the enteric nervous system (ENS), a key regulator of gastrointestinal (GI) motility, in these modifications remains largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 28 publications
10
54
0
5
Order By: Relevance
“…Remarkably, enteric neuron subtype plasticity appears to continue after birth, at least in rodents, in which close proximity of the developing ENS to bowel lumen facilitates diet and intestinal microbe-induced changes in neuronal cell fate (102). In rats, the percentage of ChAT-IR neurons in colon myenteric plexus increases from P14 to P36, whereas the percentage of nNOS-IR neurons increases from P1 to P5 and then remains unchanged to P36 (103). These ratios can be altered by intraluminal lipids.…”
Section: Ens Morphogenesis Does Not End When Encdcs Reach "The End"mentioning
confidence: 99%
“…Remarkably, enteric neuron subtype plasticity appears to continue after birth, at least in rodents, in which close proximity of the developing ENS to bowel lumen facilitates diet and intestinal microbe-induced changes in neuronal cell fate (102). In rats, the percentage of ChAT-IR neurons in colon myenteric plexus increases from P14 to P36, whereas the percentage of nNOS-IR neurons increases from P1 to P5 and then remains unchanged to P36 (103). These ratios can be altered by intraluminal lipids.…”
Section: Ens Morphogenesis Does Not End When Encdcs Reach "The End"mentioning
confidence: 99%
“…During later postnatal development, the intestinal epithelial barrier surface increases, and the paracellular permeability per surface of the intestinal epithelial barrier decreases (13,27). In rats, the proportion of myenteric neurons in the colon increases during the first weeks of the postnatal period, which is likely related to the development of colonic spontaneous motility (31). During the suckling and weaning periods, the composition of the diet and the amount of dietary input modulate structural and functional development of the intestine due to a direct effect on genes that determine this structural and functional development (2).…”
mentioning
confidence: 99%
“…In adult guinea pigs, caffeine can also induce intestinal smooth muscle relaxation Articles by facilitating the inhibitory responses to isoprenaline, cyclic 3'-5'-adenosine mono-phosphate, and papaverine (18). Rodents are a suitable animal model to evaluate the caffeine effect on preterm neonates given that at birth their gastrointestinal function is developmentally comparable to 32-wk gestation infants (31). In this study, we demonstrated that the caffeine-induced relaxant effect in newborn rat gastric muscle is equally dependent on ryanodine receptors.…”
Section: Discussionmentioning
confidence: 99%